Rescuing the planet : protecting half the land to heal the Earth - Hiss, Tony (Alfred A. Knopf, 2021)
"From the veteran New Yorker staff writer and award-winning author of The Experience of Place: an urgent, resounding call to protect half the earth's land--and thereby millions of its species--by 2050, that gives us the tools to think big about the planet and our role in conserving it. Beginning in the North American Boreal Forest that stretches through Canada, and roving across the continent from the Northern Sierra to Alabama's Paint Rock Forest to a ranch in Mexico, Tony Hiss sets out on a journey to take stock of the "superorganism" that is the earth: its land, its elements, its occupants, its greatest threats, and what we can do to keep it, and ourselves, alive. He invites us to understand not only the scope and gravity of the problems we face in this challenge, but just why protecting half the land is the way to fix them, introducing us to the many institutions and organizations already involved in the fight, such as the Indigenous Leadership Initiative, the Yellowstone to Yukon Conservation Initiative, and the global animal tracking project ICARUS. Throughout these pages, we encounter engineers, geologists, biologists, botanists, oceanographers, ecologists, and other "Half Earthers" like Hiss, as he gleans their insights, weaving together a vast network of experts in what amounts to an incredible, and incredibly illuminating, work of synthesis: what E. O. Wilson, in his introduction, calls "as clear a picture of humanity's impact on earth's natural environment as ever written." Tender, impassioned, curious, and above all else inspiring, 50 by '50 is a work that promises to make all of us better citizens of the earth"--